Touchscreens for Aircraft Navigation Tasks: Comparing Accuracy and Throughput of Three Flight Deck Interfaces Using Fitts' Law. (September 2020) - van Zon, Nout C. M.; Borst, Clark; Pool, Daan M.; van Paassen, Marinus M.
Objective: Use Fitts' law to compare accuracy and throughput of three flight deck interfaces for navigation. Background: Industry is proposing touch-based solutions to modernize the flight management system. However, research evaluating touchscreen eﬀectiveness for navigation tasks in terms of accuracy and throughput on the flight deck is lacking. Method: An experiment was conducted with 14 participants in a flight simulator, aimed at creating Fitts' law accuracy and throughput models of three different flight deck interfaces used for navigation: the mode control panel, control display unit, and a touch-based navigation display. The former two constitute the conventional interface between the pilot and the flight management system, and the latter represents the industry-proposed solution for the future. Results: Results indicate less accurate performance with the touchscreen navigation display compared to the other two interfaces and the throughput was lowest with the mode control panel. The control display unit was better in both accuracy and throughput, which is found to be largely attributed to the tactile and physical nature of the interface. Conclusion: Although performance in terms of accuracy and throughput was better with the control display unit, a question remains whether, when used during a more realistic navigation task, performance is still better compared to a touch-based interface. Application: This paper complements previous studies in the usage of aircraft touchscreens with new empirical insights into their accuracy and throughput, compared to conventional flight deck interfaces, using Fitts' law.